Research on magnetic tracking and positioning technology for automatic driving in coal mine - YANG Li (Gong-kuang zidonghua, 2022)
Most auxiliary transportation vehicles in coal mine adopt wireless positioning method, and the dynamic positioning precision is more than 3 m. This method can not meet the requirements of automatic driving vehicles positioning precision in coal mine. The response time of real-time vehicle positioning data is more than 400 ms, which cannot meet the requirements of automatic driving vehicles for real-time acquisition of positioning information. In order to solve the above problems, a magnetic tracking and positioning technology for automatic driving in coal mine is proposed. The magnetic induction antenna device is arranged at a suitable position of the automatic driving vehicle for auxiliary transportation. Several numbered passive induction magnetic nails are arranged on the vehicle driving route. When the induction antenna passes through the passive induction magnetic nails, the passive induction magnetic nails generate pulse signals under the action of the magnetic field of the induction antenna. The specific position of the pulse signal generation position within the magnetic field range of the magnetic induction antenna can be obtained in real time. The positioning information is forwarded by the magnetic induction antenna to vehicle control system through the CAN bus communication interface. According to the relative position of the center point of the magnetic induction antenna and the passive induction magnetic nail, the control system calculates the deviation position between the position of the vehicle's roadway and the center of the driving route through the batch informed tree (BIT*) algorithm. Therefore, the purpose of positioning and tracking is achieved. In order to verify the effectiveness of the magnetic tracking and positioning technology, an industrial test is carried out in Shenmu Zhangjiamao Coal Mine of Shaanxi Coal Group. Magnetic nails are arranged in a single row with equal spacing in conventional sections. According to different application requirements, the combination of 5 rows of 4 magnetic nails and 2 rows of 5 magnetic nails is used to arrange passive induction magnetic nails in mine well,roadway turn and before and after destination of vehicles route. This method realizes the millimeter-level high precision, millisecond-level low latency, and effective tracking and positioning of the automatic driving vehicle. And it enables the automatic driving vehicle to accurately drive to the destination according to the optimal path.